Overcoming resistance through novel drug targets - Coates, Anthony (Henry Stewart Talks, 2009)
Urgent need for new antibiotics, Why are so few antibiotics reaching the market, Pharmaceutical companies leaving the research arena, Targets, Bacterial molecules (genomics), Problems with the genomic approach, Bacteriophage, Treatments and problems with bacteriophages, Whole bacteria, Conventional multiplying bacteria, Non-culturable bacteria, Non-multiplying bacteria, Tuberculosis, bacterial endocarditis, catheter infections and prosthesis infections, Ways of making new antibiotics against whole live bacteria, Potential advantages and problems of making new antibiotics which kill non-multiplying and multiplying bacteria, Standardization